2017
DOI: 10.15252/embj.201796516
|View full text |Cite
|
Sign up to set email alerts
|

The FTD‐like syndrome causing TREM2 T66M mutation impairs microglia function, brain perfusion, and glucose metabolism

Abstract: Genetic variants in the triggering receptor expressed on myeloid cells 2 (TREM2) increase the risk for several neurodegenerative diseases including Alzheimer's disease and frontotemporal dementia (FTD). Homozygous TREM2 missense mutations, such as p.T66M, lead to the FTD-like syndrome, but how they cause pathology is unknown. Using CRISPR/Cas9 genome editing, we generated a knock-in mouse model for the disease-associated Trem2 p.T66M mutation. Consistent with a loss-of-function mutation, we observe an intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
181
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(200 citation statements)
references
References 81 publications
19
181
0
Order By: Relevance
“…At least some of the GRN ‐dependent FTLD‐associated phenotypes can be mimicked in a mouse model entirely lacking PGRN (Ahmed et al , ; Yin et al , ; Wils et al , ; Gotzl et al , ). Furthermore, both, a Trem2 knockout and the knockin of the p.T66M mutation, mimic features of a FTD‐like syndrome (Kleinberger et al , ; Mazaheri et al , ). Since both proteins are preferentially expressed in microglia, we compared loss‐of‐PGRN‐associated microglial phenotypes with those known for TREM2 deficiency (Krasemann et al , ; Mazaheri et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At least some of the GRN ‐dependent FTLD‐associated phenotypes can be mimicked in a mouse model entirely lacking PGRN (Ahmed et al , ; Yin et al , ; Wils et al , ; Gotzl et al , ). Furthermore, both, a Trem2 knockout and the knockin of the p.T66M mutation, mimic features of a FTD‐like syndrome (Kleinberger et al , ; Mazaheri et al , ). Since both proteins are preferentially expressed in microglia, we compared loss‐of‐PGRN‐associated microglial phenotypes with those known for TREM2 deficiency (Krasemann et al , ; Mazaheri et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Signaling is terminated by proteolytic shedding of the TREM2 ectodomain (Kleinberger et al , ; Schlepckow et al , ). Several sequence variants associated with TREM2 cause neurodegeneration via a loss of function (Kleinberger et al , , ; Schlepckow et al , ; Ulland et al , ; Song et al , ). Sequence variants of TREM2 affect a multitude of functions including chemotaxis, migration, survival, binding of phospholipids and ApoE, proliferation, survival, and others (Kleinberger et al , , ; Atagi et al , ; Bailey et al , ; Wang et al , ; Yeh et al , ; Mazaheri et al , ; Ulland et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we [70] and others [71] previously found that microglial loss-of-function mutations in TREM2 affect energy metabolism throughout the entire brain. Again, a rather small percentage of brain cells seemed to influence metabolism throughout the entire brain.…”
Section: Discussionmentioning
confidence: 97%
“…In this issue of The EMBO Journal, Kleinberger et al (2017) provide intriguing evidence suggesting a TREM2 mutation alone can lead to striking microglial dysfunction and precipitate changes in cerebral blood flow and metabolism in mice. In this issue of The EMBO Journal, Kleinberger et al (2017) provide intriguing evidence suggesting a TREM2 mutation alone can lead to striking microglial dysfunction and precipitate changes in cerebral blood flow and metabolism in mice.…”
Section: Geneticmentioning
confidence: 98%